Metformin use on the risks of depression and anxiety in people with type 2 diabetes - Meijuan Kang; Huan Liu; Jingni Hui; Yifan Gou; Ruixue Zhou; Ye Liu; Chen Liu; Panxing Shi; Bingyi Wang; Yan Wen; Bolun Cheng; Yumeng Jia; et al. (Communications Medicine)
Abstract Background: Many studies have shown that metformin may benefit mental health, but its genetic relevance remains unclear. The balance between metformin’s mental benefits and potential side effects has not been thoroughly explored. This highlights the need for a detailed evaluation of metformin’s impact on personalized glucose-lowering strategies in type 2 diabetes mellitus (T2DM) patients. Methods: We analyzed data from 11,379 patients with T2DM (mean age 60.16 ± 6.85 years; 68% male) from the UK Biobank to compare the risk of mental disorders between metformin users and non-users. Propensity score weighting (PSW) and multivariate Cox models were used to adjust for confounding factors. Genome-wide environmental interaction study (GWEIS) identified genes associated with metformin use and mental disorders. Time-to-benefit (TTB) for metformin-induced prevention of mental disorders was estimated using Weibull models and Monte Carlo simulations. Results: Among 11,379 participants, 1115 (9.96%) are diagnosed with depression and 896 (7.93%) with anxiety. Metformin use significantly reduces the risk of depression (PSW: 0.771, 95% CI: 0.649–0.916). GWEIS identifies multiple significant genes with interaction effects between metformin use and depression, such as KCNIP4 (P = 7.69 × 10−17) and BTG3 (P = 9.58 × 10−16). TTB results show that 1 case of depression is prevented per 1000 patients taking metformin for 8.270 months (Absolute Risk Reduction, ARR = 0.001). Conclusions: This study reveals the potential protective effect of metformin against depression, identifying some new candidate genes that may influence this effect. Meanwhile, patients with a life expectancy of more than 8.270 years may derive mental health benefits from metformin treatment.